General model of leadership by roles in the Peruvian context. Exploratory study on directing spirit in Peru - Acevedo Borrego, Adolfo (2016)
Systemic Leadership is the ability to communicate and influence the perception, vision, expectations and actions of people, it’s an invisible process management that unifies business systems giving a sense of direction and future of the organization running. Within the academic environment, the missions of schools focused on processes pose professional leadership as one of its important elements, on the other hand, preliminary studies define the professional and uncommunicative, submissive and less able to influence. The study of leadership in Peru shows how the various theories, behavioral traits process, contingency, that do not match reality in the Peruvian context, the lack of research evidence. The aim of the present study is that leadership is a temporary role, a role taken by the scene, position and problematic situation of decision manager. The research is empirical and exploratory comprises the conceptual model of leadership roles and quantitative corroboration of the hypothesis a sample of managers. The findings indicate that leadership is temporary, varies by the vision and position of the person, establishing a leaderfollower relationship for commitment or benefits, temporarily manifested by the stage performance of persons. No clear guidance is perceived to some kind of leadership role, this requires further study in specific contexts referring to change of leadership role when the scene changes.